Analysis of Students' Difficulties in Solving Story Problems for Whole Number Subtraction - Palayukan, Hersiyati; Langi', Evy Lalan; Palengka, Inelsi (Universitas Negeri Surabaya, 2025)
Mengkendek in solving word problems involving whole number subtraction. The research employed a qualitative case study approach, using test items, interviews, and documentation as instruments. Four students who answered all test items incorrectly were selected as participants. The data collection techniques included written tests and semi-structured interviews. The analysis reveals that the main difficulties faced by students include: (1) limited understanding of mathematical language, resulting in failure to relate story contexts to mathematical operations; (2) visual perception challenges, such as difficulty visualizing abstract concepts into numeric forms; and (3) language comprehension problems, particularly in understanding terms like “less than” or “borrowing.” These difficulties hinder students from interpreting and solving mathematical problems correctly.